2002
DOI: 10.1098/rspb.2001.1848
|View full text |Cite
|
Sign up to set email alerts
|

Pheasant sexual ornaments reflect nutritional conditions during early growth

Abstract: Differences in growth conditions during early life have been suggested to cause long-lasting effects on morphology and quality of adult birds. We experimentally investigated the effect of early growth conditions on the expression of sexual ornaments later in life in male ring-necked pheasants (Phasianus colchicus). We also investigated the effects on immune function, as it could be a functional link between early nutrition and ornament expression. We manipulated the dietary protein intake during the first eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
80
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(83 citation statements)
references
References 55 publications
1
80
2
Order By: Relevance
“…Many characters become fixed after production (e.g. avian plumage) or after maturation, but nutrition intake prior to maturation can affect the resources available to produce pigmentation or ornamentation (Ohlsson, Smith, Raberg, & Hasselquist, 2002;Taylor, Clark, & McGraw, 2011;Uetz, Papke, & Kilinc, 2002). On the other hand, energetically demanding behaviors such as elaborate courtship displays may be more strongly affected by adult (or current) diet, which has an impact on available energetic resources (Brown, 2011;Droney, 1996Droney, , 1998Dussourd, Harvis, Meiwald, & Eisner, 1991;Kolluru & Grether, 2004;Wedell, 1994).…”
mentioning
confidence: 99%
“…Many characters become fixed after production (e.g. avian plumage) or after maturation, but nutrition intake prior to maturation can affect the resources available to produce pigmentation or ornamentation (Ohlsson, Smith, Raberg, & Hasselquist, 2002;Taylor, Clark, & McGraw, 2011;Uetz, Papke, & Kilinc, 2002). On the other hand, energetically demanding behaviors such as elaborate courtship displays may be more strongly affected by adult (or current) diet, which has an impact on available energetic resources (Brown, 2011;Droney, 1996Droney, , 1998Dussourd, Harvis, Meiwald, & Eisner, 1991;Kolluru & Grether, 2004;Wedell, 1994).…”
mentioning
confidence: 99%
“…In summary, we have shown that colourful plumage grown after leaving the nest is a window on the developmental history of the male [5], in common with other avian integuments that are known to be affected by neonatal environmental conditions [8,10]. Although the mechanisms that link developmental history with colourful plumage have yet to be identified, our study adds to the diversity of secondary sexual traits whose expression is strongly linked to the environment in which they developed.…”
Section: (F ) Data Analysismentioning
confidence: 80%
“…In addition, some studies have tracked the downstream effects of developmental environment on colourful adult traits. However, these have tended to focus on non-plumage-based ornaments, such as the fleshy red wattles of ring-necked pheasants (Phasianus colchicus) [8,17], and the carotenoid-based bills of zebra finches (Taeniopygia guttata) [7,10,18,19] and mallard ducks (Anas platyrhynchos) [20]. Despite this important work, the relevance of developmental conditions for colourful adult plumage is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations